IN-OVO INJECTION OF Citrus aurantifolia EXTRACT AT DAY 18 OF INCUBATION: EFFECTS ON INCUBATION TRAITS, HATCHABILITY, GROWTH PERFORMANCE, AND HAEMATOLOGICAL INDICES OF ISA BROWN LAYER CHICKS - Dogara, Muhammad Umar; Sani, Sani M.; Abdullahi, Ramalan H.; Mundi, Harirat L.; Abdullahi, Zainab (FUDMA Journal of Sciences, 2026)
This study evaluated the effects of in-ovo injection of extract of Citrus aurantifolia administered at day 18 of incubation-on-incubation characteristics, hatchability traits, post-hatch growth performance (to day 28), and haematological indices of ISA Brown layer chicks. A fresh matured Citrus aurantifolia seeds were air-dried at room temperature for 3 weeks and extraction was done using water and ethanol. A total of 360 fertile eggs (120 eggs per treatment; 3 replicates of 40 eggs each) were assigned to three treatments: uninjected control (0 µg/ml; T1), 0.4 µg/ml extract (T2), and 0.6 µg/ml of Citrus aurantiifolia seed extract (T3). Percentage egg weight loss (PEWL) was determined between 0–12, 12–18, and 0–18 d of incubation. Hatchability, chick yield, hatch residue analysis, growth performance, and day-old haematology were evaluated. Data were subjected to analysis of variance. There was significantly (P ≤ 0.05) reduction of PEWL across incubation periods. Whereas hatchability and chick yield were not significant (P > 0.05). Chicks from T3 showed improved feed conversion ratio (FCR) and higher packed cell volume (PCV), haemoglobin (Hb), and red blood cell (RBC) counts. However, dead chick percentage increased at the higher dose. These findings indicate that low-volume in-ovo administration of C. aurantifolia extract (CASE) can enhance physiological status and feed efficiency of ISA Brown chicks, although proper dose adjustment is needed.
Keywords: in-ovo injection; Citrus aurantifolia; ISA Brown; hatchability; haematology